The Importance of Digital Literacy in Improving Students' Skills in English - Putra, Dhanu Ario; Rullyanti, Merry (Journal Of Dehasen Educational Review, 2023)
Pandemic Indonesia believes that Indonesians still experience "technology stuttering", especially in the education sector, where technology is scarce due to the availability of technological equipment. The phenomenon of pandemic situations makes online learning difficult for teachers and students because they do not have enough skills to implement online learning. This affects the quality of the learning process and the results of students in school, especially in English subjects. The purpose of this study is to observe the digital literacy skills of high school students in Bengkulu. This study was based on descriptive qualitative semi-structured interviews to investigate 21 students. The use of digital literacy in learning English was used in those interviews, and the results of the interviews are discussed in the journal. Digital literacy is a student's ability to search for information on the Internet. In addition, digital literacy allows students to choose information carefully. This study shows the student's ability to find appropriate information in their English material. In addition, this study explains the importance of digital literacy, especially for ESL students, and how to use English digital literacy in the post-pandemic situation in Indonesia.